The Influence of Transformational Leadership, Competence, and Career Development on Job Satisfaction and Their Implementation on Employee Performance : (Survey at the State Printing Company of the Republic of Indonesia, Jakarta) - Suyatin Suyatin; Azhar Affandi; Hamsinah Hamsinah; Jaja Suteja; Heru Setiawan (International Journal of Social Sciences, 2026)
This study investigates the impact of transformational leadership, competence, and career development on job satisfaction and employee performance at the State Printing Company of the Republic of Indonesia (PNRI) in Jakarta. The research adopts a quantitative approach with survey methods involving 134 PNRI employees. It explores the relationship between leadership styles, employee competencies, and career development opportunities in shaping job satisfaction, which, in turn, influences employee performance. The findings indicate that transformational leadership does not significantly affect job satisfaction, while competence and career development both positively influence job satisfaction. Furthermore, job satisfaction is found to have a significant and positive effect on employee performance. However, transformational leadership negatively impacts employee performance, suggesting that its application requires more careful management to avoid undermining performance. Competence, surprisingly, shows no direct influence on employee performance, while career development exhibits a positive effect on performance. The results emphasize the need for a stronger focus on career development and job satisfaction to improve employee performance. It also highlights the importance of refining leadership strategies to better align with organizational needs, especially in the face of digital transformation challenges in the printing industry. Recommendations include fostering a supportive leadership style, enhancing employee competencies through continuous training, and establishing clear career pathways to boost job satisfaction and performance at PNRI.